PERFORMANCE COMPARISON OF TUNING METHODS FOR NAPHTHA KEROSENE SPLITTER COMPOSITION CONTROL - Ramadhan Seba, Rafi
A distillation column is a commonly used separation method that is energy intensive. A distillation column process is complex; hence it is important to have simulation data available to simulate distillation column operation in the field which will save time and money as the process is energy intensive. This study will use an NKSU whose process configuration is a total condenser, with a reboiler of an external heat exchanger with forced circulation. The product of the top will be the Stabilized Naphtha and the bottom is Kerosene. This study is done by performing a dynamic simulation of a Naphtha Kerosene Splitter Unit (NKSU) in ASPEN HYSYS V11 to evaluate the performance of composition controllers in two composition control configurations and with two tuning methods. The composition control configurations are top and bottom product compositions controlled by indirect material balance, and the other configuration consists of an indirect and direct material balance control. The study will evaluate the performances when there are process feed disturbances of feed flowrate changes at constant naphtha kerosene ratio and feed naphtha kerosene ratio disturbance change at constant feed flow, as well as setpoint step and ramp changes. The results show that the performance of Ziegler Nichols (ZN) tuning method is superior at handling disturbances compared to the Tyreus Luyben (TL) tuning method using the performance integral criteria. The integral criteria value is smaller for ZN, which means that it is better at suppressing errors and is more stable at handling disturbances. While the high degree of interaction composition control has lower general error than the limited degree of interaction composition control, due to its significantly high error at handling naphtha ratio content changes the high degree of interaction is not recommended for use in real conditions over the limited degree of interaction composition control configuration.